Floristic links between West Coast and South Coast (South Africa) – Is the Breede River Valley a migration route? - Mucina, Ladislav; Zietsman, J.; Dreyer, L.L. (2008)
The Breede River Valley (BRV) (characterized by remarkably heterogenic landscapes) comprises several distinct vegetation types which support highly diverse floras. Moreover, this unique river valley forms a lowland link between the western and southern coastal lowland regions of Greater Capensis. Several affinities of this valley with the bordering coastal regions induced the hypothesis that the BRV might have functioned as a migration corridor for plants between the West Coast and South Coast. The main aim of this research is to characterize the patterns of floristic and vegetation diversity in the BRV through a large scale diversity assessment. In particular, vegetation types that are shared between the BRV, West and South coasts (Shale Renosterveld, Sand Fynbos and Saline vegetation units) are being investigated and compared in terms of alpha diversity, beta diversity, species composition overlap and endemism. These should enable the identification of specific habitat corridors that specific plants could have utilized for migrations. The identification of nodes of high alpha diversity and endemism throughout the study area may aid in the recognition of botanically important areas that need to be prioritized for conservation. In addition, the spatial distribution of genetic variation for populations of plant taxa with known distribution ranges that span the BRV and both the particular coastal regions are being assessed. The distribution of genetic profiles of such taxa should reveal migration directionality through the study area.